Is Radiation-Free Ultrasound Accurate for Quantitative Assessment of Spinal Deformity in Idiopathic Scoliosis (IS): A Detailed Analysis With EOS Radiography on 952 Patients - Wong, Yi-shun; Lai, Kelly Ka-lee; Zheng, Yong-ping; Wong, Lyn Lee-ning; Ng, Bobby Kin-wah; Hung, Alec Lik-hang; Yip, Benjamin Hon-kei; Chu, Winnie Chiu-wing; Ng, Alex Wing-hung; Qiu, Yong; Cheng, Jack Chun-yiu; Lam, Tsz-ping (Ultrasound in medicine & biology, 2019)
Radiation exposure with repeated radiography required at follow-up poses serious health concerns for scoliosis patients. Although spinous process angle (SPA) measurement of spinal curvatures with ultrasound has been reported with promising results, an evidence-based account on its accuracy for translational application remains undefined. This prospective study involved 952 idiopathic scoliosis patients (75.7% female, mean age 16.7 ± 3.0 y, Cobb 28.7 ± 11.6°). Among 1432 curves (88.1%) detected by ultrasound, there was good correlation between radiologic Cobb angles measured manually on EOS (E_Cobb) whole-spine radiographs and automatic ultrasound SPA measurement for upper spinal curves (USCs) (r = 0.873, apices T7–T12/L1 intervertebral disc) and lower spinal curves (LSCs) (r = 0.740, apices L1 or below) (p < 0.001). Taller stature was associated with stronger correlation. For E_Cobb <30°, 66.6% USCs and 62.4% LSCs had absolute differences between E_Cobb and predicted Cobb angle calculated from SPA ≤5°. Ultrasound could be a viable option in lieu of radiography for measuring coronal curves with apices at T7 or lower and Cobb angle <30°.